2019
DOI: 10.1111/ejn.14646
|View full text |Cite
|
Sign up to set email alerts
|

Role for the membrane estrogen receptor alpha in the sexual differentiation of the brain

Abstract: Estrogens exert pleiotropic effects on multiple physiological and behavioral responses. Male and female sexual behavior in rodents constitutes some of the best‐characterized responses activated by estrogens in adulthood and largely depend on ERα. Evidence exists that nucleus‐ and membrane‐initiated estrogen signaling cooperate to orchestrate the activation of these behaviors both in short‐ and long‐term. However, questions remain regarding the mechanism(s) and receptor(s) involved in the early brain programmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 91 publications
1
27
0
Order By: Relevance
“…Thus, the presence of nuclear ERα early in life provides a potential mechanism for organizational effects of hormones and sex differences on striatal neuron physiology that have been previously reported (Cao et al, 2016). Nuclear ERα expression does not exclusively organize sexual differentiation of the brain as a role for membrane or extranuclear ERα has also been described (Khbouz et al, 2019). It is unclear what the role of GPER1 in the nucleus may have in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of nuclear ERα early in life provides a potential mechanism for organizational effects of hormones and sex differences on striatal neuron physiology that have been previously reported (Cao et al, 2016). Nuclear ERα expression does not exclusively organize sexual differentiation of the brain as a role for membrane or extranuclear ERα has also been described (Khbouz et al, 2019). It is unclear what the role of GPER1 in the nucleus may have in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…for membrane or extranuclear ERα has also been described (Khbouz et al, 2019). It is unclear what the role of GPER1 in the nucleus may have in cell signaling.…”
Section: Limitations To This Studymentioning
confidence: 99%
“…Our findings demonstrated an additional important role of membrane ERα in hypothalamic ERα neural populations, namely ERα ARH and ERα vlVMH neurons, in maintaining their acute responsiveness to either the ERα agonist or hypoglycemia. The role of membrane-bound ERα was also described to be important in the brain, especially for the organization of the circuits underlying sexually differentiated responses of the male brain [ 57 ]. In addition to the impaired fasting-induced refeeding, the ERα-C451A mutation also causes severe deficits in the glucose-sensing capability of ERα ARH and ERα vlVMH neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mouse studies, ERα has been shown to mediate most of the estrogenic actions in organs including the brain, endothelium, mammary gland, vagina, and uterus. ERα has also been shown to control processes such as atheroprotection, vasodilatation, nitric oxide synthesis, endothelial healing, and bone demineralization, and is also involved in the prevention of type-2 diabetes [7,[42][43][44][45][46][47][48][49]. Two distinct signaling pathways are associated with ERα activation (reviewed in [50]): the genomic/nuclear pathway [51] and the non-genomic/extranuclear/membrane-initiated steroid signaling (MISS) pathway [50,52].…”
Section: Estetrol Signaling Pathwaysmentioning
confidence: 99%